PERANAN RETRIBUSI DAN PAJAK PARKIR TERHADAP PENERIMAAN PAD KOTA KENDARI - Tadjuddin Tadjuddin (Universitas Halu Oleo, 2017)
Regional autonomy is slowly bringing the consequence of diminishing balance funds, both through DAU and DAK. Therefore, the government must optimize its revenues through Regional Original Income (PAD). Even though Kendari PAD continues to increase, but if some PAD components such as retribution are more optimized, then the PAD will experience a higher increase. The analytical method used in this research is descriptive quantitative and qualitative methods. The study population is all motorized vehicles along with owners / drivers who park and pay retribution to officers (collectors). The sampled population is the owner / driver (parking service user) and the officer (collector). The total sample of 100 motorized vehicle owners / drivers who filled out and returned the questionnaire was only 69 people. The results showed that the role of taxes and retribution for motorized vehicle parking in Kendari City was not significant. This is because there are still many tax objects / that have not been identified, parking management / management that has not been neatly arranged and supervision that has not been maximized. Similarly, parking performance is also not optimal. This can be seen in: regional revenues are still dominated by parking fees at TJU paid through STNK, the government has not provided adequate parking facilities for compensation from fees paid by the community, the discovery of some unofficial parking officers, attributes (vests and tickets) is not utilized.Â